Experimental study on heat transfer of supercritical CO2 flowing in a mini tube under heating conditions. (June 2020) - Guo, Pengcheng; Liu, Shouchun; Yan, Jianguo; Wang, Junhui; Zhang, Qiaoling
Highlights: Heat transfer of supercritical CO2 (S-CO2 ) was experimentally studied under high ratio of heat flux to mass flux ( q / G ) conditions. Heat transfer deterioration of S-CO2 and the buoyancy effect under high q / G conditions were analyzed. A number of heat transfer correlations for S-CO2 were compared with the experimental data. A new correlation was proposed to predict the heat transfer of S-CO2 under high q / G conditions. Abstract: Supercritical carbon dioxide (S-CO2 ) power cycles hold great potential applications in various energy utilization systems, in which the heat transfer of S-CO2 is one of the most important issues. However, due to the complex thermophysical properties, it is still insufficient to predict heat transfer coefficient of S-CO2, especially under the heating conditions with high ratios of heat flux to mass flux ( q / G ). In this study, the heat transfer of S-CO2 is experimentally investigated in a mini tube ( d = 2 mm) in the range of p = 7.6–8.4 MPa, q = 100–200 kW/m 2 and G = 400–700 kg/m 2 s, in which the ratio of q / G is within 250–500 J/kg. The parameter influences on heat transfer coefficient of S-CO2 are analyzed. It is found that the heat transfer coefficient decreases with increasing heat flux and decreasing mass flux, but is little affected by pressure. Under high q / G conditions, buoyancy effect is significant and heat transfer is deteriorated in the whole test section. Available heat transfer correlations for S-CO2 are compared with the experimental data; however, the prediction errors of these correlations are relatively high, especially in pseudo-critical regions. As a result, a new heat transfer correlation is developed for S-CO2 under high q / G conditions, in which buoyancy effect and variations in thermophysical properties are both taken into account.